Effect of Paratracheal Pressure on the Glottic View During Direct Laryngoscopy: A Randomized Double-Blind, Noninferiority Trial. (1st June 2021) - Won, Dongwook; Kim, Hyerim; Chang, Jee-Eun; Lee, Jung-Man; Min, Seong-Won; Ma, Seoyoung; Kim, Chanho; Hwang, Jin-Young; Kim, Tae Kyong
Abstract : BACKGROUND: Cricoid pressure has been used as a component of the rapid sequence induction and intubation technique. However, concerns have been raised regarding the effectiveness and safety of cricoid pressure. Paratracheal pressure, a potential alternative to cricoid pressure to prevent regurgitation of gastric contents or aspiration, has been studied to be more effective to cricoid pressure in preventing gastric insufflation during positive pressure ventilation. However, to adopt paratracheal compression into our practice, adverse effects including its effect on the glottic view during direct laryngoscopy should be studied. We conducted a randomized, double-blind, noninferiority trial comparing paratracheal and cricoid pressures for any adverse effects on the view during direct laryngoscopy, together with other secondary outcome measures. METHODS: In total, 140 adult patients undergoing general anesthesia randomly received paratracheal pressure (paratracheal group) or cricoid pressure (cricoid group) during anesthesia induction. The primary end point was the incidence of deteriorated laryngoscopic view, evaluated by modified Cormack–Lehane grade with a predefined noninferiority margin of 15%. Secondary end points included percentage of glottic opening score, ease of mask ventilation, change in ventilation volume and peak inspiratory pressure during mechanical mask ventilation, ease of tracheal intubation, and resistance encountered while advancing the tube into the glottis. The position of the esophagus was assessed by ultrasound in both groups to determine whether pressure applied to the respective area would be likely to result in esophageal compression. All secondary outcomes were tested for superiority, except percentage of glottic opening score, which was tested for noninferiority. RESULTS: Paratracheal pressure was noninferior to cricoid pressure regarding the incidence of deterioration of modified Cormack–Lehane grade (0% vs 2.9%; absolute risk difference, −2.9%; 95% confidence interval, −9.9 to 2.6, P <.0001). Mask ventilation, measured on an ordinal scale, was found to be easier (ie, more likely to have a lower score) with paratracheal pressure than with cricoid pressure (OR, 0.41; 95% confidence interval, 0.21–0.79; P = .008). The increase in peak inspiratory pressure was significantly less in the paratracheal group than in the cricoid group during mechanical mask ventilation (median [min, max], 0 [−1, 1] vs 0 [−1, 23]; P = .001). The differences in other secondary outcomes were nonsignificant between the groups. The anatomical position of the esophagus was more suitable for compression in the paratracheal region, compared to the cricoid cartilage region. CONCLUSIONS: Paratracheal pressure was noninferior to cricoid pressure with respect to the effect on glottic view during direct laryngoscopy.